Pemanfaatan Ekstrak Lignin Dari Kulit Jengkol (Pithecellobium jiringa) Sebagai Inhibitor Korosi Baja Lunak Dalam Medium HCl - Emriadi Emriadi; Savira Nurul Hayuni; Yeni Stiadi (Departemen Kimia Universitas Andalas, 2022)
Lignin extract from jengkol peel (Pithecellobium jiringa) as a mild steel corrosion inhibitor in 1 M HCl solution was studied using weight loss method, characterization Fourier Transform Infra Red (FTIR), Ultraviolet-Visible (UV-Vis) spectroscopy, and optical microscopy. The inhibition efficiency increased with increasing temperature and the concentration of lignin extract in 1 M HCl solution. The highest efficiency value was 90,1% with the addition of 10 g/L extracts at 60°C. The adsorption of lignin extract from jengkol peel followed the Langmuir adsorption isotherm. Thermodynamic parameters such as Gibbs energy (ΔG), enthalpy (ΔH), entropy (ΔS), and activation energy were calculated to determine the mechanism of corrosion inhibition. FTIR analysis and UV-Vis spectroscopy showed an interaction between lignin extract from jengkol peel and mild steel surface. Optical microscopy analysis showed that lignin extract from jengkol peel could reduce the formation of rust on the steel surface.